1990
DOI: 10.1002/nau.1930090504
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle exercise for the treatment of female stress urinary incontinence: II. Validity of vaginal pressure measurements of pelvic floor muscle strength and the necessity of supplementary methods for control of correct contraction

Abstract: Abbreviations used: PFM = pelvic floor muscles; SUI = stress urinary incontinence. 0 1990 Wiley-Liss, Inc. 480 BB et al.simultaneous observation of inward movement of the balloon catheter. Vaginal pressure rise due to simultaneous contraction of other muscles is probably not larger than pressure rise due to intended PFM contraction. Reinforced balloon tip will not change pressure recording, and rise in EMG activity of lower abdominal muscles seems unavoidable during maximal PFM contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
158
0
9

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 245 publications
(170 citation statements)
references
References 6 publications
3
158
0
9
Order By: Relevance
“…The findings in this paper therefore add weight to the belief that black women have PFM that are better equipped to withstand the effect of intra-abdominal forces on the urinary tract and thus are less likely to experience SUI [1] Similar results were found if the PFM strength of the white students of this study when compared to strength measurements of continent physiotherapy students in Norwegian studies [24][25][26][27]. Moreover, other studies evaluating vaginal squeeze pressure in continent women reported values in the same area, which compares favourably with values of mixed-race and white women in the present study [18,28]. However, caution must be exercised when direct comparisons are made as measurements have been done with different measuring apparatus [15] Mean maximal contraction values for women with SUI or mixed incontinence have much lower reported values (5-16.2 cmH 2 O) [16,26,26,[29][30][31].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The findings in this paper therefore add weight to the belief that black women have PFM that are better equipped to withstand the effect of intra-abdominal forces on the urinary tract and thus are less likely to experience SUI [1] Similar results were found if the PFM strength of the white students of this study when compared to strength measurements of continent physiotherapy students in Norwegian studies [24][25][26][27]. Moreover, other studies evaluating vaginal squeeze pressure in continent women reported values in the same area, which compares favourably with values of mixed-race and white women in the present study [18,28]. However, caution must be exercised when direct comparisons are made as measurements have been done with different measuring apparatus [15] Mean maximal contraction values for women with SUI or mixed incontinence have much lower reported values (5-16.2 cmH 2 O) [16,26,26,[29][30][31].…”
Section: Discussionsupporting
confidence: 87%
“…Contractions were accepted as correct, when the PI assessed that no visible co-contraction of hip adductor, gluteal or rectus abdominus muscles (posterior pelvic tilt) took place and the catheter was drawn inwards while the participant performed the PFM contraction [16]. The method has been tested for intratester reproducibility and has been found to be reliablei [14,18] Procedure: Two sets of 3 maximum voluntary contractions of the PFM were recorded. The participants were instructed to maintain three PFM contractions up to 10 seconds with a rest period of 20 seconds between each contraction.…”
Section: Recruitment Of Participantsmentioning
confidence: 99%
“…16 The patients were requested to ''lift and squeeze the PFM as hard as possible.'' The co-contraction of the gluteal, hip adductor and rectus abdominal muscles was discouraged.…”
Section: Methodsmentioning
confidence: 99%
“…5,6,22 Digital palpation is not considered a reproducible or valid method for measuring the PFM strength, 17 and peak pressure of manometry should not be used alone. 16 Therefore, it is noteworthy for clinical practice that the combined use of both methods has a good correlation.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Women scheduled for delivery at Akershus University Hospital, Norway from January 2010 until April 2011 were invited to participate when they attended their routine ultrasound examination at mid-pregnancy (gestational week [18][19][20][21][22]. Background information on presence and level of bother of dyspareunia were collected through an electronic questionnaire at 5 differ-ent time points; pre-pregnancy, at gestational weeks 22 and 37, and at 6 and 12 months postpartum.…”
Section: Participantsmentioning
confidence: 99%